Improving The Students’ Reading Comprehension in Narrative Text By Using Concept Oriented Reading Instruction - Daulay, Sholihatul Hamidah (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This study aims to improve students' reading comprehension in narrative texts through the use of concept-oriented reading instruction strategies. The subject of this study was her 8th grade student in his SMA N 1 in 2017. This study of this study was conducted using a classroom behavioral study. The data used in this study is based on pre-test results, interview sheets, and observation sheets to know before and after the test. The study found that the number of students reading narrative texts increased. The pretest average was 39.80. The first cycle average was 87.86, indicating that the first cycle results and averages were superior to the pre-test. The percentage of students who did not score above 75 also increased. Three of her students (11%) passed or scored up to 75 on the pretest. On the Cycle I posttest, 26 of her students (100%) scored 75 or higher, an increase of approximately 89%. In other words, the students' reading comprehension of the narrative texts improved more and more from the first session to the next. The calculated t-test formula was used for hypothesis testing. We found that the observed coefficient t(16.63) > ttable(1.708). Therefore, the alternative hypothesis (Hα) may be accepted. Based on this finding, the alternative hypothesis (Hα) states that the CORI strategy may improve students' reading comprehension of narrative texts.